2015
DOI: 10.1074/jbc.m114.635870
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemotactic Protein-induced Protein 1 and 4 Form a Complex but Act Independently in Regulation of Interleukin-6 mRNA Degradation

Abstract: It was recently demonstrated that MCPIP1 is a critical factor that controls inflammation and immune homeostasis; however, the relationship between MCPIP1 and other members of this protein family is largely unknown. Here, we report that MCPIP1 interacts with MCPIP4 to form a protein complex, but acts independently in the regulation of IL-6 mRNA degradation. In an effort to identify MCPIP1-interacting proteins by co-immunoprecipitation (Co-IP) and mass-spec analysis, MCPIP4 was identified as a MCPIP1-interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…The identity of MCPIP1 containing granules is still controversial. We recently found that MCPIP1-containing granules overlapped with GW182 and argonaute 2 (AGO2), which are molecular markers of GW-bodies, suggesting that MCPIP1 may functionally interact with microRNA effector pathways 38 . However, a recent study indicated that MCPIP1 was localized on ribosomes on endoplasmic reticulum 32 .…”
Section: Ccch Zinc Finger Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identity of MCPIP1 containing granules is still controversial. We recently found that MCPIP1-containing granules overlapped with GW182 and argonaute 2 (AGO2), which are molecular markers of GW-bodies, suggesting that MCPIP1 may functionally interact with microRNA effector pathways 38 . However, a recent study indicated that MCPIP1 was localized on ribosomes on endoplasmic reticulum 32 .…”
Section: Ccch Zinc Finger Proteinsmentioning
confidence: 99%
“…Similarly, monocyte chemotactic protein-induced protein 1 (MCPIP1) interacts with GW182, another core component of miRISC 38 . However, the functional significance of the interaction of these CCCH zinc finger proteins with miRISC is still an open question.…”
Section: Ccch Zinc Finger Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…MCPIP1 seems to form a homodimer and a homotetramer upon binding to the targeted stem‐loop . However, MCPIP1 was shown to interact with MCPIP4 (Zc3h12d), and it is likely that they can form a heterotetramer in order to expand their range of substrates, gain specificity, or increase activity . MCPIP1 targets TRAF proteins by de‐ubiquitination and impairs their function in the inflammatory and immune response .…”
Section: Introductionmentioning
confidence: 99%
“…Zc3h12d −/− mice synthesize increased amounts of IL‐2, IL‐6, and IL‐10 and overexpression of ZC3H12D results in a faster decay of IL‐2, IL‐6, IL‐10, TNF, IL‐17A mRNAs in Jurkat cells and destabilizes IL‐1β, IL‐6, and TNF transcripts in THP1 cells [Minagawa et al, , Zhang et al, ]. Recently, it was published that ZC3H12D interacts with ZC3H12A forming a protein complex present in the cytoplasm in granule‐like structures, enriched with markers typical for GW‐bodies [Huang et al, ].…”
mentioning
confidence: 99%